Corporate social responsibility (csr) in the tile factory industry in Tlambah Karang Village, Penang, Sampang: Case Study UD. Junior Baru - Fatimah; Muhtadi M, Ridan; Harizah, Siti (NUsantara Islamic Economic Journal, 2024)
Corporate social responsibility (CSR) is a social and environmental responsibility that is a company's commitment to participate in sustainable economic development in order to improve the quality of life and a beneficial environment, both for the company itself, the local community and society in general. D Company. Junior Baru is a micro, small and medium enterprise company operating in the roof tile industry that carries out corporate social responsibility (CSR). The purpose of this research is to determine the implementation and results of CSR at UD. Junior Baru Tlambah Karang Penang Sampang. The approach used in this research is a qualitative data analysis method with a case study approach. With the research location at the UD Junior Baru tile factory company. This type of research uses field study research. This type of research uses field study research. This was chosen because this research was carried out by conducting direct research in the field to obtain accurate data. Data collection techniques are: observation, interviews and documentation. The research results provide actual results of the implementation of corporate social responsibility (CSR) in the roof tile factory industry at UD. Junior Baru in Tlambah Village, Karang Penang District, Sampang Regency, has been implemented, including a Mosque renovation program, providing building materials for Madrasas or schools, and obstacles in implementing corporate social responsibility are the lack of CSR funds and lack of community concern, it has not been running optimally and evenly because it is still It is necessary to improve the responsibilities in company supervision.